Disclosure of intimate partner violence by men and women in Dar es Salaam, Tanzania - Christopher, Enryka; Drame, Ndeye D.; Leyna, Germana H.; Killewo, Japhet; Bärnighausen, Till; Rohr, Julia K. (Frontiers in Public Health, 2022)
Intimate Partner Violence (IPV) has severe health consequences, though may be underreported due to stigma. In Tanzania, estimates of IPV prevalence range from 12 to >60%. List experiments, a technique of indirectly asking survey questions, may allow for more accurate prevalence estimates of sensitive topics. We examined list experiment and direct questions about experiences of physical and sexual IPV from a 2017 cross-sectional survey among 2,299 adults aged 40+ years in Dar es Salaam. List experiment prevalence estimates were determined through quantitative analysis and compared qualitatively to direct question prevalence estimates. The list experiment estimated a higher prevalence of IPV in all cases except for physical violence experienced by women. This study contributes to the estimation of IPV prevalence. If the list experiment estimates yield an unbiased estimate, findings suggest women openly report experiencing physical IPV, and IPV experienced by men is underreported and understudied.
Gesehen am 09.01.2023